FAKTOR YANG MEMPENGARUHI CARA BELAJAR MAHASISWA BIMBINGAN DAN KONSELING ANGKATAN 2011 DI STKIP PGRI SUMATERA BARAT - Sari, Eka Puspita; Kasih, Fitria; Yasmi, Fifi (Bimbingan dan Konseling, 2014)
How to learn Student Counseling Program ( BK ) in West Sumatra STKIP PGRI influenced by internal and external factors . Based on the phenomenon the researchers raised concerns about the study : factors affecting student learning . The purpose of this study to identify and describe ( 1 ) Internal factors that affect student learning guidance and counseling in 2011 at STKIP PGRI West Sumatra , ( 2 ) external factors that affect student learning guidance and counseling in 2011 at STKIP PGRI West Sumatra. This research is descriptive . The population in this study were all students of Guidance and Counseling STKIP PGRI West Sumatra active class of 2011 enrolled in classes totaling 325 students . Sampling technique is used in simple random sampling done by random sampling , regardless of the strata ( level ) . Sample C is a session and the first session totaled 72 people . The research instrument was a questionnaire , used for data analysis techniques percentage. The results of the study revealed that : 1 ) The internal factors affecting student learning is (a) Health factors are many categories , namely 51.39 % . ( b ) the readiness factors are many categories , namely 56.94 % . ( c ) The motivation factor was quite a lot of categories , ie 54.17 % . ( d ) The factors of interest were quite a lot of categories , ie 58.33 % . 2 ) External factors affecting student learning guidance and counseling consists of ( 1 ) family environmental factors are enough categories , ie 48.61 % . ( 2 ) the environmental factors studied were quite a lot of categories , ie 61.11 % . ( 3 ) factors milieu are many categories ,namely 61.11 % .